A COMPARATIVE STUDY ON UNDERSTANDING LEGAL LOOPHOLES IN LAW NUMBER 1 OF 2024 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS RELATED TO DEFAMATION - Moch. Haidar Ali Al Hamid; Suratman; Moh. Muhibbin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to comparatively examine legal regulations related to criminal defamation occurring through social media during the regional head election (Pilkada) campaign period in Lamongan Regency. This study refers to the provisions of Law Number 7 of 2023 concerning Elections, which explicitly prohibits acts of insult or defamation during the election process. On the other hand, there are also regulations governing similar crimes in the electronic domain, as stipulated in Law Number 1 of 2024 concerning Electronic Information and Transactions (UU ITE). This study employs a qualitative approach with a comparative method to analyze the changes, advantages, and weaknesses in the provisions of the latest ITE Law, particularly in the context of political dynamics during the Pilkada campaign period in Lamongan Regency. The analysis shows that Law Number 1 of 2024 provides a more detailed and firm definition and limitations for the crime of defamation on social media. This regulation more clearly establishes the threshold for legal violations and the applicable sanctions, thereby creating greater legal certainty. These findings are expected to serve as a reference for law enforcement in strengthening legal protection for victims of defamation against individuals in the digital era.